Nghiên cứu tổng hợp và chuyển hóa 6-axetyl-5-hidroxi-4-metylcumarin và 6-axetyl-7- hidroxi-4-metylcumarin - Thảo, Nguyễn Minh; Vinh, Nguyễn Văn; Toản, Trần Quốc; Chỉnh, Nguyễn Đức (Vietnam Journal of Chemistry, 2014)
By the acetylation of resorcinol by acetic acid and ZnCl2 has been obtained 2,4-dihydroxyacetophenone, which in reaction with ethyl acetoacetate to give 6-acetyl-5-hydroxy-4-methylcoumarine or 6-acetyl-7-hydroxy-4-methylcoumarine. By condensation of 6-acetylcoumarines derivatives with aromatic aldehydes have been prepared the series of α,β-unsaturated ketones. Antimicrobial and antifungal activities of these compounds have been investigated. Structure of these products have been determined by IR, 1H-NMR and MS spectroscopies